PERCUTANEOUS NEEDLE PERITONEAL BIOPSY IN THE DIAGNOSIS OF EXUDATIVE ASCITES - Mahmood, Khalid; Saeedi, Mohammad Ilyas; Mohammad, Riaz; uddin, Zia; Kamal, Mustafa (Journal of Ayub Medical College Abbottabad, 2008)
Background: Percutaneous needle peritoneal biopsy in diagnosis of exudative ascites has gained wide acceptance and many workers have utilized it with a high diagnostic yield and no significant complications. Present study has been carried out to determine the efficacy of percutaneous needle peritoneal biopsy in the diagnosis of exudative ascites of unknown aetiology. Methods: It is a descriptive case study conducted in Medical '˜C' Unit, Lady Reading Hospital, Postgraduate Medical Institute, Khyber Medical University Peshawar over a period of 2 years, i.e., from Nov, 2003 to December 2005. A total of 45 patients having unexplained exudative ascites underwent blind needle peritoneal biopsy. The biopsy specimen was subjected to histopathology. Ascitic fluid was also obtained for analysis. Post biopsy patients were observed for 24 hours for any untoward complications. Results: A total of 45 patients (17 male and 28 female) with age range from 20 to 65 years and having exudative ascites were studied. The commonest presentation of our patients was abdominal distension (93.3%), pain abdomen (46.67%), fever (44.4%) and weight loss (33.3%). Histopathology of the peritoneal biopsies was reported as follows. Eighteen cases (40%) showed non specific chronic inflammation, 10 (22.2%) cases showed caseating granulomatous inflammation suggestive of tuberculosis and 6 (13.3%) cases showed metastatic adenocarcinoma. In one patient peritoneal mesothelioma was reported. In the remaining10 patients (22.2%) biopsies were either non representative or inconclusive. The ascitic fluid showed predominantly lymphocytes in 86.6% of cases. Only three patients were reported to be having atypical cells on fluid cytology. The procedure was found safe. No patient was lost due to complications related to the procedure. Only one patient had evidence of intra peritoneal bleed. The commonest problem post biopsy was pain (91.1%) and mild swelling (53.3%) at biopsy site. Conclusion: Peritoneal biopsy is fairly safe and inexpensive procedure with good diagnostic efficacy in patients with undiagnosed exudative ascites. Keywords: Peritoneal biopsy, Diagnosis, Exudative ascites